Anti-theft system and temperature control of computer equipment for laboratories and data center of the faculty of electrical and computing engineering - Irving, Valeriano C.; Harlyn, Pichardo O.; Marjorie, Chalen T.; Washington, Velasquez V. (2016 IEEE Colombian Conference on Communications and Computing (COLCOM), 2016)
This paper explains the problem that DST (Departamento de Soporte Tecnico) has to face every day, this department is responsible for managing the technology resources of FIEC (Facultad de Ingenieria Electrica y Computacion) through the process of lending computers and monitoring availably of resources. The process of lending computer equipment for students defines that every incident about lost or disconnection of any computer peripheral device must be register, but it has been made manually. This paper also provides information on the implementation of a system in order to avoid peripherals theft in laboratories and to prevent damage to servers as well as by high temperatures or excess moisture.